2017
DOI: 10.1080/09540105.2017.1333579
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trichlorfon residues in vegetables using a quantum dot-labeled biomimetic immunoassay method followed by capillary electrophoresis

Abstract: In this study, a molecularly imprinted polymer that could selectively recognize trichlorfon was synthesized. Using the imprinted polymer as biomimetic antibody, a novel biomimetic immunoassay-capillary electrophoresis method with improved sensitivity was developed for the detection of trichlorfon. This method was based on the competitive reaction between quantum dot-labeled trichlorfon and free trichlorfon with the biomimetic antibody. Under optimal conditions, the limit of detection (IC 15 ) and the sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…In several publications, a thermally reversible hydrogel was used as a buffer additive to improve reproducibility . More details about the practical applications of this format are summarized in Table .…”
Section: Homogeneous Ce Immunoassaysmentioning
confidence: 99%
“…In several publications, a thermally reversible hydrogel was used as a buffer additive to improve reproducibility . More details about the practical applications of this format are summarized in Table .…”
Section: Homogeneous Ce Immunoassaysmentioning
confidence: 99%
“…General reviews of the studies can be found elsewhere [38,39]. Moreover, because QDs exhibit strong absorption in the UV-vis region, they were also employed in CE-UV detection [40].…”
Section: Fluorescence Detectionmentioning
confidence: 99%
“…The preparation of trichlorfon hapten was followed by our previous study (Jiang, Wu, Xu, Qiao, & Xu, 2017). Firstly, 5.66 g of trichlorfon (22 mmol) and 2.00 g of succinic anhydride (20 mmol) were dissolved in 5 mL of anhydrous pyridine.…”
Section: Trichlorfon Haptenmentioning
confidence: 99%